Factors Affecting Weight Gain in Hormonal Contraceptive Users at Midwife's Independent Practice in Cibatu Village - Kartina, Delina; cahyati, yanti; Rohmatin, Etin (Media Informasi, 2025)
Background: Indonesian Health Profile data in 2023 shows that most acceptors prefer hormonal contarceptors. Using injectable contraceptives was 35.3%, followed by pills at 13.2%, and implants at 10.5%. The use of hormonal contraception causes various side effects such as menstrual disorders, dizziness, nausea, and headaches, and also increases weight in the recipient. Objective: to discover the factors affecting weight gain in hormonal contraceptive users. Method: the method used is observational with a cross-sectional approach. The population of all women of childbearing age who use hormonal contraception in TPMB midwife N is 160 people. 62 respondents obtained the sampling technique using Slovin. The research instrument used a questionnaire to determine the influence of age factors, physical activity, diet, and length of use on the weight gain of birth control acceptors. Results: age p-value (0.016), physical activity p-value (0.017), diet p-value (0.002), length of use p-value (0.011). Conclusion: There is a relationship between age, physical activity, diet, and length of use with weight gain in hormonal contraceptive users.